Olympiada Gold Deposit, Yenisei Ridge, Russia - Sazonov A.M.; Lobanov K.V.; Zvyagina E.A.; Leontiev S.I.; Silyanov S.A.; Nekrasova N.A.; Nekrasov A.Y.; Borodushkin A.B.; Poperekov V.A.; Zhuravlev V.V.; Ilyin S.S.; Kalinin Yu.A.; et al. (My University, 2020)
The Olympiada deposit, containing >1,560 metric tons (t; 50 Moz) of gold at an average grade of 4 to 4.6 g/t Au, occurs in central Siberia, Russia. Over 30 years, the deposit produced more than 580 t of gold, including 200 t from oxidized ore grading 11.1 g/t. The deposit forms a 2-km-long, steeply dipping system, which is traced downdip for 1.7 km. It occurs in the Neoproterozoic orogen of the Yenisei Ridge at the western margin of the Siberian craton. This and other gold deposits in the district are controlled by the large, long-lived Tatarka-Ishimbino tectonic zone, marking a suture between terranes chiefly consisting of deformed Meso- to Neoproterozoic carbonate-clastic sedimentary rocks. The combination of lithologic and structural factors was critical for localization of gold mineralization associated with calcic and siliceous alteration accompanied by early arsenic and late antimony sulfides. As a result, very fine (10 μm) and high fineness (910–997) gold associates with diverse sulfides, especially arsenopyrite, and commonly contains mercury, similar to some characteristics of Carlin-type deposits. Geochronologic studies suggest that mineralization was formed during several stages between 817 and 660 Ma. The isotopic composition of Os and He, along with presence of anomalous Ni, Co, and Pt, points to a mantle mafic source, whereas isotopic composition of Pb and S suggest a contaminated crustal source, i.e., originating from a mix of mantle and crustal fluids.
Keywords: Olympiada deposit; gold; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская